(untitled) (European Journal of Pure and Applied Mathematics, 2018)
Considered dynamical system is a flow of clusters with the same length l on contours of unit length connected in polar-remote points into closed chain. When clusters move trough common node, the left-priority rule of conflict resolution works. In the paper it is shown that in the case of chain consisted third contours the dynamical system has a spectrum of velocity and mode periodicity consisted on not more two components. Distribution of spectrum in dependence on load l is developed. Hypothesis on discrete spectrum in the case of arbitrary number of contours are formulated.